2017
DOI: 10.1002/adv.21927
|View full text |Cite
|
Sign up to set email alerts
|

Effects of composition and temperature of initial mixture on the formation and properties of polyurethane foam

Abstract: The purpose of the study is to optimize the initial conditions of the molding process of a multicomponent mixture into a refrigerator cabinet. Polyurethane foaming has been studied with different starting compositions and temperatures of the initial mixture. The kinetic mechanism has involved four reactions and species species. Using a standard recipe, the chemical kinetics and the numerical implementation have been first validated against the experimental values of the filling time and the density of the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The results of mechanical properties tests showed that both tensile strength and modulus of polyurethane foams materials gradually decreased with the increase in preheating temperature. Özdemir [ 56 ] used different proportions of the initial mixture and initial mixture temperature (20–45 °C) for polyurethane foams foaming and the results showed that a higher initial mixture temperature can significantly reduce polyurethane foams filling time and improve foaming uniformity.…”
Section: Influence Of Temperature On Polyurethane Foam Properties Dur...mentioning
confidence: 99%
“…The results of mechanical properties tests showed that both tensile strength and modulus of polyurethane foams materials gradually decreased with the increase in preheating temperature. Özdemir [ 56 ] used different proportions of the initial mixture and initial mixture temperature (20–45 °C) for polyurethane foams foaming and the results showed that a higher initial mixture temperature can significantly reduce polyurethane foams filling time and improve foaming uniformity.…”
Section: Influence Of Temperature On Polyurethane Foam Properties Dur...mentioning
confidence: 99%
“…The foaming of PU occurs due to the release of carbon dioxide (CO 2 ) formed by reaction between isocyanate and methyl formate. [50][51][52][53][54] Moreover, the products of primary reactions react with isocyanate to produce several secondary products [55][56][57][58] shown in chemical reactions summarized Figure 2.…”
Section: Mechanism Of Foaming Processmentioning
confidence: 99%